Genetic Diversity and Population Structure of Bullet Tuna (Auxis rochei) from Bali and Its Adjacent Waters - Maya Agustina; Bram Setyadji; Made Pharmawati; I ketut Junitha (HAYATI Journal of Biosciences, 2022)
Bullet tuna (Auxis rochei) dominates the neritic tuna catch, especially from the purse seine fleet within the western and southern Indonesian waters. However, high catches can lead to stock depletion and lower genetic diversity due to possible inbreeding. Therefore, population genetic information is important in monitoring the sustainability of fish stocks and proposing an appropriate species-specific conservation strategy. This study aimed to analyze the genetic diversity, population structure, and kinship relationship of bullet tuna in Bali and its adjacent waters. Sampling was carried out in September 2020 at landing sites/ports representing the north, east, south, and west region, whereas at least 30 samples were acquired at each location. The result showed that the DNA concentration obtained could produce DNA bands with allele length ranged from 94-260 bp. Observed heterozygosity (Ho) was around 0.440-0.627. While the expected heterozygosity (He) was between 0.932-0.945. The genetic variation among population, within-population, and individuals was 0.36%, 41.04%, and 58.60%, respectively. The results of the analysis of genetic diversity between individuals in the population showed very high genetic diversity. The population structure of the bullet tuna landed in West Bali, East Bali, South Bali and North Bali is the same population stock. The kinship relationship indicates that the four populations are closely related genetically.